Middle cerebral artery blood flow velocity during a 4 km cycling time trial - Rattray, B.; Smale, B. A.; Northey, J. M.; Smee, D. J.; Versey, N. G. (European Journal of Applied Physiology, 2017)
Purpose: This study sought to describe middle cerebral artery blood flow velocity (MCAv) during a 4 km cycling time trial, and relate it to different pacing strategies adopted by participants. Methods: After familiarisation and a standardised exercise protocol, 15 male trained cyclists rode a 4 km time trial on a cycling ergometer. MCAv was assessed via transcranial Doppler ultrasound in the right hemisphere at resting baseline, and throughout the time trial. Mean arterial pressure, end-tidal partial pressure of carbon dioxide (PetCO2) and heart rate were assessed alongside MCAv. Plasma lactate was assessed post time trial. Data were compared depending upon whether participants completed the time trial with a positive (first half faster than the last) or negative pacing profile although there was no difference in the time to completion with either pacing strategy (positive 344 ± 23 s, negative 334 ± 14 s; p = 0.394). Results: Lower mean MCAv (positive pacing -7.6 ± 14.2%, negative pacing +21.2 ± 15.0% compared to resting baseline measures; p = 0.004) and lower PetCO2 (significant interaction p < 0.001) towards the end of the time trial were observed with positive compared to negative pacing. Heart rate and lactate did not differ between pacing strategies. Conclusions: Changes in MCAv appear to depend on the pacing strategy adopted, with a positive pacing strategy likely to contribute to a hyperventilatory drop in PetCO2 and subsequent reduction in MCAv. Although lower cerebral blood flow cannot be directly linked to an inability to raise or maintain power output during the closing stages of the time trial, this potential contributor to fatigue is worth further investigation.